Validation of newly developed and redesigned key indicator methods for assessment of different working conditions with physical workloads based on mixed-methods design : A study protocol - Andre Klussmann and Falk Liebers and Felix Brandstädt and Marianne Schust and Patrick Serafin and Andreas Schäfer and Hansjürgen Gebhardt and Bernd Hartmann and Ulf Steinberg (BMJ open, 2017)
Introduction The impact of work-related musculoskeletal disorders is considerable. The assessment of work tasks with physical workloads is crucial to estimate the work-related health risks of exposed employees. Three key indicator methods are available for risk assessment regarding manual lifting, holding and carrying of loads; manual pulling and pushing of loads; and manual handling operations. Three further KIMs for risk assessment regarding whole-body forces, awkward body postures and body movement have been developed de novo. In addition, the development of a newly drafted combined method for mixed exposures is planned. All methods will be validated regarding face validity, reliability, convergent validity, criterion validity and further aspects of utility under practical conditions. Methods and analysis As part of the joint project MEGAPHYS (multilevel risk assessment of physical workloads), a mixed-methods study is being designed for the validation of KIMs and conducted in companies of different sizes and branches in Germany. Workplaces are documented and analysed by observations, applying KIMs, interviews and assessment of environmental conditions. Furthermore, a survey among the employees at the respective workplaces takes place with standardised questionnaires, interviews and physical examinations. It is intended to include 1200 employees at 120 different workplaces. For analysis of the quality criteria, recommendations of the COSMIN checklist (COnsensus-based Standards for the selection of health Measurement INstruments) will be taken into account. Ethics and dissemination The study was planned and conducted in accordance with the German Medical Professional Code and the Declaration of Helsinki as well as the German Federal Data Protection Act. The design of the study was approved by ethics committees. We intend to publish the validated KIMs in 2018. Results will be published in peer-reviewed journals, presented at international meetings and disseminated to actual users for practical application.
Keywords: key indicator method; NIOSH lifting equation; OCRA; risk assessment; strain index; work-related musculoskeletal disorders